PGC-1α-mediated imbalance of mitochondria-lipid droplet homeostasis in neomycin-induced ototoxicity and nephrotoxicity - Bin Chen; Cheng Cheng; Yunhao Wu; Siyu Li; Mo Han; Le Zhen; Ying Peng; Suhan Guo; Kaidi Shen; Xia Gao; Renjie Chai; Guangji Wang; et al. (Elsevier, 2024)
Ototoxicity and nephrotoxicity are the most prevalent side effects of aminoglycoside antibiotics (gentamicin, amikacin, neomycin) and platinum anti-tumor drugs (cisplatin, carboplatin). The inner ear and kidney share similarities in drug deposition and toxicity, but the underlying pathophysiological mechanisms remain unclear. Investigating the shared mechanisms and metabolic alterations in these distinct organs will provide valuable insights for clinical therapy. A strong correlation has been identified between the spatiotemporal accumulation patterns of neomycin and the specific occurrence of lipid metabolism disorders in these two organs. The primary allocation of neomycin to mitochondria results in a notable escalation in the accumulation of lipid droplets (LDs) and more interactions between mitochondria and LDs, leading to a sequence of disturbances in lipid metabolism, such as increased lipid ROS and the blocked transfer of fatty acids from LDs to mitochondria. PGC-1α deficiency worsens the neomycin-induced disorders in lipid metabolism and intensifies the pathological interactions between mitochondria and LDs, as indicated by the exacerbated disturbance of dynamic LD turnover, increased level of oxidized lipids and decreased use of fatty acids. This investigation provides a fresh perspective on the lipid metabolic dysfunction related to mitochondria-LD interactions in drug-induced ototoxicity and nephrotoxicity, potentially providing novel avenues for intervention strategies.